1976
DOI: 10.1002/cpt1976203253
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin bioavailability: Formulations and rates of infusions

Abstract: The bioavailability of digoxin (lanoxin) tablets, oral aqueous solution of digoxin, and capsules containing a solution of digoxin was compared with digoxin given intravenously over 1 and 3 hr. The mean peak serum concentration of digoxin after the 1-hr intravenous infusion was 5 ng/ml, after the 3-hr infusion, 3.5 ng/ml, and after the oral solution, 2.0 ng/ml. There was an equivalent bioavailability of the oral solution and reference tablets of digoxin. The digoxin in capsules tended to be better absorbed than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 1 publication
3
5
0
Order By: Relevance
“…This phenomenon has been reported previously in relation to digoxin bioavailability studies (Greenblatt, Duhme, Koch-Weser & Smith, 1974;Marcus, Dickerson, Pippin, Stafford & Bressler, 1976), and may be due to alterations in clearance which are dependent on the precise mode of administration. Marcus et al (1976) reported that 21% more digoxin was excreted in the urine over 6 days after a 3 h intravenous infusion than after a 1 h infusion. Greenblatt et al (1974) also observed this effect when they found a greater 6 day urinary excretion of digoxin after a 1 h infusion compared with a rapid intravenous injection.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This phenomenon has been reported previously in relation to digoxin bioavailability studies (Greenblatt, Duhme, Koch-Weser & Smith, 1974;Marcus, Dickerson, Pippin, Stafford & Bressler, 1976), and may be due to alterations in clearance which are dependent on the precise mode of administration. Marcus et al (1976) reported that 21% more digoxin was excreted in the urine over 6 days after a 3 h intravenous infusion than after a 1 h infusion. Greenblatt et al (1974) also observed this effect when they found a greater 6 day urinary excretion of digoxin after a 1 h infusion compared with a rapid intravenous injection.…”
Section: Discussionsupporting
confidence: 72%
“…An interesting discrepancy revealed by the results was the significant difference in the bioavailability fraction calculated from serum and from urinary excretion data, the latter giving higher values. This phenomenon has been reported previously in relation to digoxin bioavailability studies (Greenblatt, Duhme, Koch-Weser & Smith, 1974;Marcus, Dickerson, Pippin, Stafford & Bressler, 1976), and may be due to alterations in clearance which are dependent on the precise mode of administration. Marcus et al (1976) reported that 21% more digoxin was excreted in the urine over 6 days after a 3 h intravenous infusion than after a 1 h infusion.…”
Section: Discussionsupporting
confidence: 72%
“…Our data (Table IV) show that 6 day urinary excretion after rapid iv injection, 67.5% of the dose, was significantly greater than after 1 hr infusion, 50% of the dose, and the coefficient of variation, 6.53%, after rapid iv injection was much less than the corresponding value of 22.4% following 1 hr infusion. So far as ratios are concerned, results obtained in our study agreed with those reported by Marcus et al (2). They reported that 60, 70, and 51% of the dose (ratios of 1.0, 1.17, and 0.85) were excreted in the urine in 6 days following 1 hr infusion, 3 hr infusion and oral solution, respectively; whereas in our study, the corresponding values (row 2 of Table IV) were 50, 58, and 36% of the dose (ratio 1.0, 1.16 and 0.72) for the same routes of administration, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Marcus et al (2) administered 0.4 mg doses of digoxin to five normal volunteers both as a constant rate infusion over 1 hr and as an infusion over 3 hr with 0.1 mg of the digoxin being infused during the first hour, 0.2 mg being infused during the second hour, and 0.1 mg being infused during the third hour. They reported: "The most striking finding in our study was that the 6 day urinary excretion of digoxin after a 3 hr infusion was 21% more than after the same dose of drug given during the 1 hr infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Transporter DDI for Glecaprevir and Pibrentasvir by renal excretion, and does not undergo significant enterohepatic circulation (Marcus et al, 1976;Lloyd et al, 1978). Thus, the digoxin AUC may only be increased a maximum of 25%-67% by inhibition of intestinal efflux, which affects bioavailability, not clearance-increases up to 150% have been reported upon coadministration with dronedarone and likely reflect additive inhibition of digoxin renal tubular secretion (Hori et al, 1993;Vallakati et al, 2013).…”
Section: Discussionmentioning
confidence: 99%